Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Define a Pseudo-Riemannian Metric $g$ in $\mathbb{R}^{n+1}$ by $g(u,v)=-u_0v_0+u_1v_1+...+u_nv_n$, where $u=(u_0,u_1,...u_n)$. Let $\eta\in\mathbb{R}^{n+1}$ be a vector such that $g(\eta,\eta)=-1$. Is it possible to find a basis $(\eta,w_1,...,w_n)$ of $\mathbb{R}^{n+1}$ such that $g(w_i,w_j)=\delta_{ij}$ and $g(\eta,w_i)=0$ for $i,j=1,..,n$

Thanks

share|cite|improve this question
    
What happens when you try the standard basis of $\mathbb{R}^{n+1}$? – Neal Nov 27 '12 at 21:24
    
Note that i fixed $\eta$ @Neal. If for example $\eta=(-1,0,...,0)$ then we can use the standard basis. – Tomás Nov 27 '12 at 21:25
    
What if $\eta = (1,0,\cdots,0)$? What is $g(\eta,\eta)$ then? – Neal Nov 27 '12 at 21:27
    
$g(\eta,\eta)=-1$ – Tomás Nov 27 '12 at 21:28
    
Misread your question - sorry about that. – Neal Nov 28 '12 at 0:08
up vote 3 down vote accepted

Your desired basis exists. Let $\eta^T=(a,v^T)$. You are essentially asking if there exist a real matrix $C$ and a real vector $u$ such that the following equality holds: $$ \begin{pmatrix}a&v^T\\u&C^T\end{pmatrix} \begin{pmatrix}-1\\&I_n\end{pmatrix} \underbrace{\begin{pmatrix}a&u^T\\v&C\end{pmatrix}}_{\color{red}{M}} =\begin{pmatrix}-1\\&I_n\end{pmatrix}.\tag{$\ast$} $$ If so, then the columns of $M$ are the desired basis vectors. Note that the LHS of $(\ast)$ is equal to $$ \begin{pmatrix}a&v^T\\u&C^T\end{pmatrix} \begin{pmatrix}-a&-u^T\\v&C\end{pmatrix} =\begin{pmatrix}-1&-au^T+v^TC\\-au+C^Tv&C^TC-uu^T\end{pmatrix}. $$ Since $g(\eta,\eta)=-a^2+\|v\|^2=-1$, we see that $a\ge1$. Hence $(\ast)$ is equivalent to the system of equations \begin{align} & C^TC-uu^T=I_n,\tag{1}\\ & u = \frac{1}{a}C^Tv.\tag{2} \end{align} Substitute (2) into (1), we get $$ C^T\left(I_n - \frac{1}{a^2}vv^T\right)C=I_n. $$ Now, from $g(\eta,\eta)=-a^2+\|v\|^2=-1$, we also get $1-\frac{\|v\|^2}{a^2}=\frac{1}{a^2}$. Therefore $I_n-\frac{1}{a^2}vv^T$ is positive definite and it has a positive definite square root. Hence we may simply take $$ C=C^T=\left(I_n - \frac{1}{a^2}vv^T\right)^{-1/2} =I+\left[\left(1-\frac{\|v\|^2}{a^2}\right)^{-1/2}-1\right]\frac{vv^T}{\|v\|^2} $$ (with $C=I$ when $v=0$). Using the equality $\|v\|^2=a^2-1$, we further obtain $C=I+(|a|-1)\frac{vv^T}{\|v\|^2}=I+\frac{vv^T}{|a|+1}$ and also $u=\frac{1}{a}C^Tv=\frac{|a|}{a}v$. So, you may obtain the desired basis vectors from the columns of $$ M=\begin{pmatrix}a&\frac{|a|}{a}v^T\\v&I+\frac{vv^T}{|a|+1}\end{pmatrix}. $$

share|cite|improve this answer
    
Thanks you, nice calculation. – Tomás Nov 28 '12 at 10:17

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.